Low bone mineral density and renal malformation in Mexican patients with Turner syndrome are associated with single nucleotide variants in vitamin D-metabolism genes. (2nd September 2019) - Barrientos-Rios, Rehotbevely; Frias, Sara; Velázquez-Aragón, José A.; Villaroel, Camilo E.; Sánchez, Silvia; Molina, Bertha; Martínez, Angélica; Carnevale, Alessandra; García-de-Teresa, Benilde; Bonilla, Edmundo; Alvarado-Araiza, Christian David; Valderrama-Hernández, Alejandro; et al.
Abstract: Turner syndrome (TS) is a common genetic disorder. TS-phenotype includes short stature, gonadal dysgenesis, cardiac and kidney malformations, low bone mineral density (low-BMD) and thyroiditis. TS-phenotype varies from patient to patient and the cause is not clear, the genomic background may be an important contributor for this variability. Our aim was to identify the association of specific single nucleotide variants in the PTPN22, VDR, KL, and CYP27B1 genes and vitamin D-metabolism, heart malformation, renal malformation, thyroiditis, and low-BMD in 61 Mexican TS-patients. DNA samples were genotyped for SNVs: rs7975232 ( VDR ), rs9536282 ( KL ), rs4646536 ( CYP27B1 ), and rs1599971 ( PTPN22 ) using the KASP assay. Chi-square test under a recessive model and multifactorial dimensionality reduction method were used for analysis. We found a significant association between renal malformation and the rs9536282 ( KL ) variant and between rs4646536 ( CYP27B1 ) and low-BMD, these variants may have modest effects on these characteristics but contribute to the variability of the TS phenotype. In addition, we identified gene–gene interactions between variants in genes KL, CYP27B1 and VDR related to vitamin D-metabolism and low-BMD in TS-patients. Our results support the idea that the genetic background of TS-patients contributes to the clinical variability seen in them.